Bringing Botany into Focus: Addressing Plant Blindness in Undergraduates Through an Immersive Botanical Experience. (16th September 2020) - Colon, Jessica; Tiernan, Nichole; Oliphant, Simone; Shirajee, Ateev; Flickinger, Jonathan; Liu, Hong; Francisco-Ortega, Javier; McCartney, Melissa
Abstract: Undergraduate science, technology, engineering, and math students (STEM) are usually not attuned to the intricacies of plant life histories or to the dynamic role plants play in ecosystems and human society, a phenomenon termed plant blindness. Botany education has declined in the past decades, whereas career paths that need and benefit from a workforce with botanical knowledge have increased. Consequently, there is a need to reduce plant blindness among undergraduate students, regardless of their career trajectories. We provide evidence that participation in a botanical experience as part of a general biology course can positively shift undergraduates' perception of botany, the study of plants. Students participating in the botanical experience showed significant positive shifts in their ability to connect botany to their college major and future careers. In addition, we show qualitative data indicating a new respect for plants and a new appreciation for the diversity among plants.